2017
DOI: 10.1016/j.jelectrocard.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of planarity of the spatial QRS loop by three dimensional vectorcardiography: Its emergence and loss

Abstract: AimsTo objectively characterize and mathematically justify the observation that vectorcardiographic QRS loops in normal individuals are more planar than those from patients with ST elevation myocardial infarction (STEMI). MethodsVectorcardiograms (VCG) were constructed from three simultaneously recorded quasiorthogonal leads, I, aVF and V2 (sampled at 1000 samples/sec). The planarity of these QRS loops was determined by fitting a surface to each loop. Goodness of fit was expressed in numerical terms. Results15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…Quasi-orthogonal: Repeated discussions (Cortez et al, 2014; Ray et al, 2017) suggested that instead of orthogonal algebraic reconstruction, vectorcardiographic loops might be obtained from standard ECG leads oriented in approximately perpendicular directions. Therefore, instead of the orthogonal XYZ leads obtained from the transformation, vector magnitude was calculated using the quasi-orthogonal leads II, V 2 , and V 5 , that is:…”
Section: Methodsmentioning
confidence: 99%
“…Quasi-orthogonal: Repeated discussions (Cortez et al, 2014; Ray et al, 2017) suggested that instead of orthogonal algebraic reconstruction, vectorcardiographic loops might be obtained from standard ECG leads oriented in approximately perpendicular directions. Therefore, instead of the orthogonal XYZ leads obtained from the transformation, vector magnitude was calculated using the quasi-orthogonal leads II, V 2 , and V 5 , that is:…”
Section: Methodsmentioning
confidence: 99%
“… 18 The QRS non-planarity has previously been investigated mainly in relation to ischaemic heart disease and myocardial infarction. 3 18 19 Although about 60% of the patients of the study suffered from ischaemic heart disease, multivariable Cox regression analysis showed that the predictive value of QRS loop non-planarity was independent of heart disease aetiology. T wave loop abnormalities have also been repeatedly studied using different characteristics.…”
Section: Discussionmentioning
confidence: 92%
“…It has previously been reported that in physiological ECG recordings, the vectorcardiographic (VCG) loops of the QRS complex are essentially planarly, 3 that is, that the three-dimensional QRS dipole moves practically in a single plane the orientation of which depends on the position of the organ. Similar observations were also made for the VCG loop of the T wave.…”
Section: Introductionmentioning
confidence: 99%
“…ЭхоКГ То, что в норме пространственная петля QRS лежит в одной плоскости, объясняют тем, что компоненты электрической волны в сердце и в окружающей среде распространяются в трех взаимно перпендикулярных направлениях равномерным образом; скорость их распространения в любом направлении остается почти постоянной и однородной [4,6].…”
Section: таблица 2 значения индекса планарности у больных им в зависи...unclassified
“…Наши данные об уменьшении планарности петли QRS у больных ИМ совпадают как с давними [7,8,9], так и с более современными работами [5,6]. Данные литературы об изменениях планарности петли QRS при ИМ разных локализаций достаточно противоречивы.…”
Section: таблица 2 значения индекса планарности у больных им в зависи...unclassified